2010
DOI: 10.1111/j.1365-2982.2009.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in nerve fibre density in human sigmoid colon circular muscle occurs with growth but not aging

Abstract: In human sigmoid colon circular muscle, there are reductions in nNOS-, VIP- and SP-IR nerve fibre density with growth from newborn to late adolescence but little further change with aging. The reduction in nerve density is due to an increase in circular muscle thickness rather than a loss of nerve fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Preclinical studies in the guinea pig colon have also shown that aging has been associated with a decrease in neurons in the ENS; however, a fall in density rather than the number of myenteric neurons is thought to be the major change with age [8]. Although data from humans to investigate age-related changes in the colon are limited, recent evidence from human sigmoid colon circular muscle suggests that a decrease in nerve fiber density occurs with growth in response to an increase in circular muscle thickness that occurs during early childhood to adolescence; however, this study found no further changes were observed with aging [9]. Moreover, the effect of age on the ENS of the human colon was recently studied in 16 patients (7 females and 9 males) with no underlying colonic disease and aged between 33 and 99 years.…”
Section: Enteric Innervationmentioning
confidence: 64%
“…Preclinical studies in the guinea pig colon have also shown that aging has been associated with a decrease in neurons in the ENS; however, a fall in density rather than the number of myenteric neurons is thought to be the major change with age [8]. Although data from humans to investigate age-related changes in the colon are limited, recent evidence from human sigmoid colon circular muscle suggests that a decrease in nerve fiber density occurs with growth in response to an increase in circular muscle thickness that occurs during early childhood to adolescence; however, this study found no further changes were observed with aging [9]. Moreover, the effect of age on the ENS of the human colon was recently studied in 16 patients (7 females and 9 males) with no underlying colonic disease and aged between 33 and 99 years.…”
Section: Enteric Innervationmentioning
confidence: 64%
“…Histological assessments of aged baboon colon supports loss of intestinal integrity and barrier function in the absence of clinical of histological evidence of disease (28). Histological quantitation of colonic smooth muscle in people and rats do not show reductions with age (29, 30). We cannot determine whether the loss of normal propulsive activity precedes loss of barrier function, or if barrier dysfunction leads to motility changes.…”
Section: Discussionmentioning
confidence: 98%
“…3) and in four regions from FAP patient 2. Nerve fibre percentage area in the circular muscle was measured in circular muscle (and therefore nerve fibre bundles) in cross sections as previously described (Peck et al 2009;Southwell et al 2010). The percentage area of nerve fibres was calculated from the number of pixels above threshold/ total number of pixels in the region of interest×100%.…”
Section: Confocal Imagingmentioning
confidence: 99%